2005
DOI: 10.1590/s1806-83242005000100003
|View full text |Cite
|
Sign up to set email alerts
|

Influence of root embedment material and periodontal ligament simulation on fracture resistance tests

Abstract: The aim of this study was to evaluate the influence of the embedment material and periodontal ligament simulation on fracture resistance of bovine teeth. Eighty bovine incisor teeth were randomized into 8 groups (n = 10), embedded in acrylic or polystyrene resin using 4 types of periodontal ligament simulation: 1--absence of the ligament; 2--polyether impression material; 3--polysulfide impression material; 4--polyurethane elastomeric material. The specimens were stored at 370C and 100% humidity for 24 hours. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
257
1
12

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 266 publications
(273 citation statements)
references
References 12 publications
3
257
1
12
Order By: Relevance
“…The simulation of the periodontal ligament should be done with an elastomeric material that is able to undergo elastic deformation and reproduce the accommodation of the tooth in the alveolus, providing no concentration of stresses in the cervical region of the tooth (10). Moreover, simulation of the periodontal ligament is highly influential on the fracture pattern (10). In this experiment, a polyether impression material was used in association with a polystyrene resin as an adequate method for fracture strength tests (10,16).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The simulation of the periodontal ligament should be done with an elastomeric material that is able to undergo elastic deformation and reproduce the accommodation of the tooth in the alveolus, providing no concentration of stresses in the cervical region of the tooth (10). Moreover, simulation of the periodontal ligament is highly influential on the fracture pattern (10). In this experiment, a polyether impression material was used in association with a polystyrene resin as an adequate method for fracture strength tests (10,16).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, simulation of the periodontal ligament is highly influential on the fracture pattern (10). In this experiment, a polyether impression material was used in association with a polystyrene resin as an adequate method for fracture strength tests (10,16). The method used for loading is another important factor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This would then result in displacement of the tooth during testing. Previous studies even showed that periodontal ligament simulation could change the fracture strength results and failure modes in a positive way in that the ligament could serve as a shock absorber [28,29]. In previous studies while some did not fill the canal [30], others did fill the canals with endodontic filling materials [3,6,16].…”
mentioning
confidence: 99%
“…20 The coronal portion of each tooth was sectioned 15 mm coronally from the root apex, using a diamond double-faced disk # 7020 (KG Sorensen, Barueri, Brazil).…”
Section: Methodology Sample Preparationmentioning
confidence: 99%